DIETS OF MICROPTERUS SALMOIDES LAC. AND ESOX LUCIUS L. IN LAKE TRASIMENO (UMBRIA, ITALY) AND THEIR DIET OVERLAP. - LORENZONI M.; CORBOLI M.; DÖRR A. J.M.; GIOVINAZZO G.; SELVI S.; MEARELLI M. (Knowledge and Management of Aquatic Ecosystems, 2002)
The aim of this study was to gather information about the feeding habits of Micropterus salmoides Lac., an exotic species recently introduced into Lake Trasimeno and Esox lucius L., in order to determine the degree of overlap between the two diets. The stomachs of 179 largemouth basses and 125 pikes were examined. The index of diet overlap (α) was determined by using a Prominence Value (PV) of each food item, using Schoener’s formula. The value of the diet overlap index in the whole sample was 0.79. When the sample was divided in groups based on length, the index values were high and varied from a minimum of 0.623 to a maximum of 0.925. Based on theses results, a hypothesis of food competition between the two species in Lake Trasimeno could not be rejected.